EFFICIENT USE OF SOLAR ENERGY RECEIVERS WITH LIQUID AND AIR AS HEAT CARRIERS - Velimir Šćekić (Journal of Engineering & Processing Management, 2013)
Reduction of fossil - iscrpljivih, but also non-renewable, fuels and increased concentrations of greenhouse gases on a global scale, have led to rapid development of alternative energy sources, resulting in the use of solar energy occupies an important role in the production of energy from renewable sources. The paper presents the system and method of absorption of solar energy collectors koncetrišućim, and its application in the world every year become more pronounced. The fact that it will be this way until the year 2040 to produce about 20% of world electricity consumption, additionally imposes the requirement that the method of obtaining energy special attention, especially because of the fact that it is less - more, this resource available to all parts of planet.
Keywords: energy; solar; solar collectors; air; liquid